Pendidikan Kesehatan Tentang Kecukupan ASI Eksklusif pada Ibu Menyusui di UPTD Puskesmas Sungai Durian Tahun 2026 - Miftah Chairunnisa; Ummy Khairussyifa (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
Breast milk (ASI) is the best source of nutrition for newborns because it contains complete, safe, and stable nutrients, thus supporting optimal growth and development of infants. However, some breastfeeding mothers still do not fully understand the sufficiency of breast milk and its benefits for babies. Therefore, health education efforts are needed to improve the knowledge and understanding of breastfeeding mothers regarding breastfeeding. Health education is an educational activity aimed at inviting and encouraging the community to be willing to take actions that can maintain and improve health. This health education activity on the sufficiency of breast milk for breastfeeding mothers was held on January 24, 2026, at the Sungai Durian Community Health Center (UPTD). The method used in this activity was the delivery of material through health counseling accompanied by a measurement of the level of knowledge using pretest and posttest questionnaires. After the presentation of the material, breastfeeding mothers were asked to complete a posttest questionnaire to assess their understanding of the material that had been provided. The measurement results showed a significant difference between the pretest and posttest scores, indicating an increase in knowledge of breastfeeding mothers after being provided with health education. Thus, it can be concluded that health education activities about breast milk sufficiency are effective in increasing the understanding of breastfeeding mothers regarding the importance of providing sufficient breast milk for babies.